Remote-controlled speedboat: comparison between plywood and fiberglass / Falah Abu and Mohd Izudin Mohamad - Abu, Falah; Mohamad, Mohd Izudin (2006)
The remote controlled is the model of toys which is popular among the children and teenagers. These models include the remote controlled car, airplane, helicopter and speedboat. The available models found in the market are made of fiberglass which more costly and not environmentally friendly. It is also available in small size but expensive because of the airplane fuel types. The purpose of this study is to make remote controlled speedboat from plywood and fiberglass which is bigger in size, cheaper and greater speed and then make comparison. Both types of speedboat are manufactured with the same dimension (122cm long x 54cm wide x 26cm high). By using the same engine capacity (52cc grass cutter engine), comparison can be made in the term of weight, speed, cost of production and method of processing.